PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI LINGKUNGAN IPDN JATINANGOR SUMEDANG JAWA BARAT - Sarjiman Arianto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2012)
Leadership is very role in society life, organization or government A leader as a movement motor or the main success of organization’s goals, moreoter in state and government life. A leader is an initiator, motivator, stimulator. dynamist and innoator in his or her organization. A good leader should reflect of good image and based on the commitment principles, credibility, integrity. consistent, not arrogant, sincere and consequent.The research design used survey method. The population consist of officers and lecturers at IPDN Subdistrict of Jatinangor Sumedang Regency. Sum of officers and lecturers samples were 62 people which consist of group IVwas as many as 8 people, group III was as many as 36 people and group II was as many as l8 people.The research result showed that :1. The leadership aspect showed good category, a leader always work on time and dong job with full of responsibility2. Working motivation aspect showed excellent. The result of respondents showed that the working spirit for public servants is very high. This case stimulates by the giving of wage, provisions, pension insurance, get higher positition, etc.3. The peroformace aspect showed excellent. In doing the job by good planning, clear working division, opened, using the cost in appropriate time, also regular controlling.Key words : that the leadership and working motivation positive influence to the public servants. Performance at IPDN Subdistrict Jatinangor Sumedang Regency